PERSEPSI GURU TERHADAP PENGELOLAAN SARANA DAN PRASARANA PEMBELAJARAN DI SMP NEGERI KECAMATAN LUBUKLINGGAU TIMUR KOTA LUBUKLINGGAU - Bobby Laventus (Universitas Negeri Padang, 2015)
The purpose of this research is to see information about the Teacher’s Perceptions of Facilities and Infrastructure Learning Management in SMP Negeri Lubuklinggau Timur. The population in this research are 168 and the sample are 35 by using simple random sampling technique. The instrument of this research is question with Likert Scale Models that had tested for validity and reliability. Data analyzed by using mean score and performance level. The result of this research are the showed that the Teacher’s Perceptions of Facilities and Infrastructure Learning Management in SMP Negeri Lubuklinggau Timur in good category. Key word : Facilities and Infrastructure Learning Management